Flathead [videorecording (DVD)] - Cumerford, Cass (Indiepix Films, 2026)
First-time director Jaydon Martin delivers a deeply personal and poetic portrait of working-class life in rural Australia. The film follows Cass, a man returning to his childhood home in Bundaberg, Queensland, after years away. As he reconnects with his old friend Andrew, Cass is forced to confront the ghosts of his past and the unspoken weight of grief, faith, and fading masculinity that haunts their lives.